2007
DOI: 10.1177/039463200702000204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Necrosis Factor-Alphaand Granulocyte Colony-Stimulating Factor Serum Levels in Lead-Exposed Smoker Workers

Abstract: Inorganic lead (Pb) is able to modulate the immune response even at low to moderate exposure levels. It inhibits in vitro and in vivo activities of neutrophilleucocytes and influences their blood count in humans. Neutrophil functions are governed by a number of cytokines. Pb has been shown to affect leukocyte production of some ofthese cytokines in vitro. The objective ofthis study is to assess serum tumor necrosis factor-alpha (TNF-a) and granulocyte colony-stimulating factor (G-CSF) levels of thirty-three ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…We demonstrated that lead exposures resulted in a dose-dependent increase of IL-8 production by PBMC as well as enhanced the production of the proinflammatory cytokines IL-6, TNF-α and the chemokines IL-8 and MIP-1α in response to mitogens. The increase in the TNF-α level was in agreement with previous studies [42] and was consistent with epidemiological data on lead-exposed workers [43]. Our observation that lead increases mitogenic activation of PBMC was in agreement with the activation of lymphocyte and leukocyte proliferation and function by lead which has been observed in earlier studies [24-27].…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that lead exposures resulted in a dose-dependent increase of IL-8 production by PBMC as well as enhanced the production of the proinflammatory cytokines IL-6, TNF-α and the chemokines IL-8 and MIP-1α in response to mitogens. The increase in the TNF-α level was in agreement with previous studies [42] and was consistent with epidemiological data on lead-exposed workers [43]. Our observation that lead increases mitogenic activation of PBMC was in agreement with the activation of lymphocyte and leukocyte proliferation and function by lead which has been observed in earlier studies [24-27].…”
Section: Discussionsupporting
confidence: 93%
“…However, the level of IL-6 did not change in this study. Similar results were obtained in lead recycling plant workers (BLL =30.7 μg/d l ), who exhibited significantly higher TNF-α than controls 19) . Our previous study on chronically Pb exposed workers (BLL=37.0 μg/d l ) demonstrated not only higher levels of TNF-α, but also higher levels of IL-6 and IL-1β 14) .…”
Section: Discussionsupporting
confidence: 84%
“…TNF-␣ is one of the principal mediators of the inflammatory responses in mammals, transuding deferential signals that regulate activation, proliferation and apoptosis at cellular levels [7]. Earlier studies identified the capacity of Pb to increase production of various pro-inflammatory cytokine mainly TNF-␣ among phagocytic cells of both animal and human [8][9][10][11][12], While the production of TNF-␣ can be elevated following exposure to lead, the expression of the receptor for TNF-␣ was also increased during the in vitro exposure of human blood monocytes to PbCl 2 [13]. Therefore, the combined effect of elevated cytokine production by macrophages and of increased receptor expression would be expected to contribute to problematic inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%